2012
DOI: 10.1002/pros.22599
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 (CCND1) expression is involved in estrogen receptor beta (ERβ) in human prostate cancer

Abstract: These findings suggest that CCND1 expression is possibly regulated by estrogens via ERβ and that this signaling pathway may influence prostate cancer development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 28 publications
2
34
0
2
Order By: Relevance
“…Similar findings were described by Nanni et al (2009); they found an association of ERb expression with a shorter disease-specific survival in patients with clinically localized HN prostate tumors. Most recently, a positive correlation between ERb and Cyclin D1, a protein with a known pro-proliferative function, has been described in HN patients (Nakamura et al 2012). Altogether, these data advocate for a more prominent role of ERb in the progression to castration resistance as thought previously.…”
Section: Discussionsupporting
confidence: 54%
“…Similar findings were described by Nanni et al (2009); they found an association of ERb expression with a shorter disease-specific survival in patients with clinically localized HN prostate tumors. Most recently, a positive correlation between ERb and Cyclin D1, a protein with a known pro-proliferative function, has been described in HN patients (Nakamura et al 2012). Altogether, these data advocate for a more prominent role of ERb in the progression to castration resistance as thought previously.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, high levels of ERβ1 did result in cell cycle arrest in early G1 phase in LNCaP cells (14). Recently, ERβ has been proposed to affect PCa acting as a cell cycle regulator, controlling the expression of cyclin D1 (CCND1) and affecting its downstream pathway (67), supporting further the notion that restoring ERβ expression may provide a new promising therapeutic approach for PCa.…”
Section: Erβ As a Useful Therapeutic Target For Pca Treatmentmentioning
confidence: 80%
“…If the H-score was >10% positive cells, it was noted as PR positive [14] . The Ki-67 and CCND1 LIs were evaluated by counting 2,000 tumor cells [17] . CCND1 immunoreactivity was subclassified into two groups, using the following criteria: 'negative' (cases with <10% positive nuclei) and 'positive' (cases with >10% positive nuclei) [17] .…”
Section: Scoring Of Immunoreactivitymentioning
confidence: 99%
“…For instance, 43% of PNETs overexpressed CCND1, which tended to be associated with advanced clinical stage [18] . CCND1 promoter was reported to be stimulated by a large number of transcription factors, mostly c-Fos and c-Jun [16,17] . Activation of CCND1 through progestin has previously been reported in breast cancer [16] , although CCND1 lacks the progesterone response element [19] .…”
mentioning
confidence: 99%
See 1 more Smart Citation